2005
DOI: 10.1016/j.ecoenv.2005.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of porewater and elutriate bivalve larval development toxicity testing in a sediment quality triad framework

Abstract: The magnitude and extent of contaminated marine sediment are frequently assessed using a Sediment Quality Triad framework involving multiple toxicity tests using a variety of species, toxicological endpoints and exposure systems. Data are integrated into an overall assessment of sediment quality using a weight of evidence approach. Guidance on the selection of appropriate toxicity tests recommends a wide range of organism type, life-cycle, exposure route, and feeding type be includedporewater bivalve larval de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…The methods used in this study did not always find toxicity at the same sites, indicating that the elutriate preparations, storage times, and subsequent bioassay tests had built-in biases. Assessing the ecological function of an aquatic system through monitoring of bottom sediment condition via elutriate testing is highly relevant (McDonald 2005), as an adequate assessment is not possible through monitoring of the water column alone. While the elutriate tests can be effective in identifying acutely toxic sites, Liß and Ahlf (1997) caution that the evaluation of elutriate toxicity alone is not sufficient to assess the potential hazard of contaminated sediments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The methods used in this study did not always find toxicity at the same sites, indicating that the elutriate preparations, storage times, and subsequent bioassay tests had built-in biases. Assessing the ecological function of an aquatic system through monitoring of bottom sediment condition via elutriate testing is highly relevant (McDonald 2005), as an adequate assessment is not possible through monitoring of the water column alone. While the elutriate tests can be effective in identifying acutely toxic sites, Liß and Ahlf (1997) caution that the evaluation of elutriate toxicity alone is not sufficient to assess the potential hazard of contaminated sediments.…”
Section: Discussionmentioning
confidence: 99%
“…Sediment elutriate tests afford a cost-effective option to bulk sediment testing and may have broad application where bulk sediment testing is not possible (Haring et al 2010). Sediment elutriates do not share the limitations of porewater to the same extent, as elutriate test methods simulate a sediment resuspension exposure via mixing of sediments with oxygenated fresh water (McDonald 2005). Some drawbacks of implementing elutriate testing include the inherent tendency of the elution process to reduce toxicity via dilution of contaminants, bias towards hydrophilic contaminants (partitioning), and decreased sensitivity via shorter exposure durations with marginally toxic samples.…”
Section: Introductionmentioning
confidence: 98%
“…Sediment elutriates from downstream areas showed no toxicity to Microtox indicating that toxic principles were not leachable in aqueous medium or their concentration eluted was lower than their toxic levels ( Table 2). Low elutriate: bulk sediment concentrations ratios have been reported in the literature as one of the factor showing no toxicity of elutriates from otherwise toxic sediment [33] and there [34][35] . This indicated that the characteristic of sediment from downstream area was of aged sediment.…”
Section: Resultsmentioning
confidence: 99%
“…A possible explanation for much less frequent detection of toxic responses in the elutriate test is dilution of toxic chemicals during the preparation of sediment elutriates. Ankley et al (1991) and McDonald (2005) examined toxicity of porewater and elutriate samples concurrently with several different organisms such as amphipods, bivalve larvae, cladocerans, fathead minnows, and oligochaetes and found that pore waters were consistently much more toxic than elutriates because of reduced toxic chemical concentrations in elutriates, demonstrating that dilution is an important factor for interpretation of elutriate test results.…”
Section: Sediment Pore Water Toxicity Testsmentioning
confidence: 99%